Autophagy from Siddhars Perspective in Preventing Non-Communicable Diseases- A Review (International Journal of Ayurveda and Pharma Research, 2023)
Siddha system of medicine is one of the ancient medicines in the AYUSH system of medicines. It described the prevention and cure of disease through the ways of "Naal Ozhukkam" (daily regimen) and "Kaala Ozhukkam” (seasonal regimen). Fasting (Pattini) is one of these practices of Naal Ozhukkam. In 2016, a Japanese man named Mr. Yoshinori Ohsumi got his Noble Prize for finding the mechanism behind autophagy. Fasting is the most efficient method of activating autophagy. This review showed fasting in our Siddha literature and autophagy from Siddhars perspective in preventing non-communicable diseases. In our Siddha literature, it says that the uses of fasting are to rest our digestive organs, remove toxins and waste products from our bodies, and refresh our body cells. Autophagy is the body’s way of eliminating damaged cells in order to regenerate newer, healthier cells. Recent research has indicated roles for autophagy in an increasing number of pathologies, from bacterial and viral infections to cancer, and more recently in neurodegenerative and other age-related diseases. But during their period, Siddhars treat fever and some other diseases by fasting. By this method, they prevent non-communicable diseases. As a result, we must lead the Siddhars' ideas by performing Naal ozhukkam and Kaala Ozhukkam to prevent non-communicable diseases.